Investigating ACF Policy Change Theory in a Unitary Policy Subsystem: The Case of Ghanaian Public Sector Information Policy - B. Timothy Heinmiller; Emmanuel M. Osei; Eugene Danso (International Review of Public Policy)
In 2019, the government of Ghana overhauled its access to public information rules through the Right to Information Act. Prior to this legislation, access to public sector information was not formally regulated and the new legislation provided a legal framework for making public sector information accessible to the general public. From an Advocacy Coalition Framework (ACF) perspective, the passage of the Right to Information Act represents a major policy change and provides a case in which the ACF theory of major policy change can be investigated. This case is also interesting because it took place in a unitary policy subsystem, as opposed to a competitive or collaborative subsystem. Unitary subsystems are characterized by a single, dominant advocacy coalition, in this case a pro-transparency coalition, and are relatively uncommon in the ACF literature. The purpose of this paper is to investigate ACF policy change theory in the Ghanaian public sector information policy subsystem – as a unitary subsystem – to determine whether it can explain the major policy change that took place with the passage of the Right to Information Act. The investigation finds strong empirical support for the ACF’s ‘pathways’ hypothesis and moderate support for the ‘power’ hypothesis.